The Influence of Financial Technology and Financial Literacy on Investment Decisions through Financial Knowledge in Gen Z in Denpasar City - Ni Nyoman Rahadianggun Netriani; Gregorius Paulus Tahu; I Made Dauh Wijana (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the influence of financial technology and financial literacy on investment decisions through financial knowledge among Generation Z in Denpasar City. The population and sample in this study consisted of all Generation Z in Denpasar City, with a sample of 100 respondents determined using the Slovin formula. Data collection was carried out through questionnaires, interviews, and documentation. Data analysis was carried out using partial least square (PLS). The results of the study show that financial technology has a positive and significant influence on the investment decisions of Generation Z in Denpasar City, financial literacy has a positive and significant influence on the investment decisions of Generation Z in Denpasar City, financial knowledge has a positive and significant influence on the investment decisions of Generation Z in Denpasar City, financial technology has a positive and significant influence on financial knowledge among Generation Z in Denpasar City, financial literacy has a positive and significant influence on financial knowledge among Generation Z in Denpasar City, financial technology has a positive and significant influence on investment decisions through financial knowledge among Generation Z in Denpasar City, and financial literacy has a positive and significant influence on investment decisions through financial knowledge among Generation Z in Denpasar City.